SINERGISME PEMANFAATAN SUMBERDAYA LOKAL DAN PEMBERDAYAAN KELOMPOK IBU-IBU DI DESA LAMUNTI PERMAI A1 KAWASAN EKS PLG KALIMANTAN TENGAH - ICHRIANI, dkk., GUSTI IRYA (Buletin Udayana Mengabdi; Vol 13 No 1 (2014): Vol 13, No 1, April 2014, 2014)
This Community Service was conducted in conjunction to the IbM programme DP2M DIKTI 2013 with the women groups of Lamunti Permai Kawasan Ex PLG, sub distric Mentangai, District Kapuas, Palangka Raya Central Kalimantan. The purposes of IbM programme (1) assist local communities in order to empower the surrounding natural resources, namely pineapple and (2) provide the skills of women to cultivate pineapple into processed food products which can become be a business opportunity for them. In late the IbM program, the group of women partners are skilled making, packing and labeling of processed pineapple products. Processed pineapple products are made in the form of crackers and wetcandied pineapples. The products were introduced to the outside Lamunti Permai. The problems encountered were the standard product could not be done in the distant location for marketing which led to increase the production costs, and moreover the production license that does not exist so that consumer confidence in processed food products is still low. Keywords: pineapple crackers, pineapple candied